2018
DOI: 10.1364/oe.26.015726
|View full text |Cite
|
Sign up to set email alerts
|

Temperature stability of thin film refractory plasmonic materials

Abstract: Materials such as W, TiN, and SrRuO (SRO) have been suggested as promising alternatives to Au and Ag in plasmonic applications owing to their stability at high operational temperatures. However, investigation of the reproducibility of the optical properties after thermal cycling between room and elevated temperatures is so far lacking. Here, thin films of W, Mo, Ti, TiN, TiON, Ag, Au, SrRuO and SrNbO are investigated to assess their viability for robust refractory plasmonic applications. These results are furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Additionally, titanium nitride has been shown to achieve enhanced hot electron harvesting relative to gold, [7,8] and indeed is reported to have long-lived hot carriers [9], although the physical origin of this phenomenon is poorly understood. TiN is also expected to be resilient to high operating temperatures [10]. The physical properties of TiN are extremely sensitive to the substitution of oxygen within its lattice, enabling also the tuning of its optical response.…”
mentioning
confidence: 99%
“…Additionally, titanium nitride has been shown to achieve enhanced hot electron harvesting relative to gold, [7,8] and indeed is reported to have long-lived hot carriers [9], although the physical origin of this phenomenon is poorly understood. TiN is also expected to be resilient to high operating temperatures [10]. The physical properties of TiN are extremely sensitive to the substitution of oxygen within its lattice, enabling also the tuning of its optical response.…”
mentioning
confidence: 99%
“…[26] It is noted that previous study has suggested that Au might be more thermally stable in air than TiN. [27] TiN grown under low temperature is CMOS compatible. [28,29] Furthermore, epitaxial TiN thin film has been previously reported grown on Si substrate by domain epitaxial matching, that is, 4 of TiN (002) match with 3 of Si (004) to overcome the very large lattice mismatch (f ≈ 24%).…”
Section: Furthermore a Waveguide Based On A Silicon Nitride (Si 3 N mentioning
confidence: 99%
“…Such refractory metals need to be structured to provide spectral selectivity 1922 . There are two major mechanisms that lead to degradation of these structures: surface diffusion 2326 and oxidation 22,2730 . The 2D and 3D structured materials contain edges on the nano scale which are subject to strong surface diffusion at temperatures below 1200 °C 25,26,3133 .…”
Section: Introductionmentioning
confidence: 99%